Strengths and limitations of before–after–control–impact analysis for testing the effects of marine protected areas on managed populations. (19th February 2019) - Kerr, Lisa A; Kritzer, Jacob P; Cadrin, Steven X
Abstract: Marine protected areas (MPAs) are a common management strategy for conserving marine resources, but it can be challenging to evaluate their effectiveness for meeting management objectives. Measuring the effectiveness of MPAs is particularly challenging in dynamic and changing environments where other management approaches are simultaneously implemented. Before–after–control–impact (BACI) analysis is a tool that offers a simple and robust design for evaluating complex effects. However, design and interpretation of a BACI analysis is not always straightforward. The goal of this study was to explore the potential for BACI to evaluate MPA performance in a system simultaneously impacted by other management measures and environmental change. We develop a typology of interpretations of BACI results based on the main and interaction effects of the model, categorized by the extent to which dynamics inside and outside of the MPA are independent. Furthermore, we examine how decisions about the spatial and temporal design of the study, and the focal species and response variables, can determine which outcomes from within the typology are evident through BACI applications to New England groundfish area closures. We identify strengths and limitations of the BACI approach and demonstrate that BACI is a valuable but imperfect tool for evaluating MPAs.